The cherry orchard : a comedy in four acts - Stanitsyn, Viktor, 1897-1976.; Chekhov, Anton Pavlovich, 1860-1904.; Coe, Richard L. (Richard Livingstone), 1914-1995; City Center of Music and Drama (New York, N.Y.); Richard L. Coe Theater Programs Collection (Library of Congress) (London : Heinemann, 1965)
New York City Center, S. Hurok presents in cooperation with City Center of Music and Drama, Moscow Art Theatre, founded by Konstantin Stanislavsky and Vladimir Nemirovich-Danchenko, "The Cherry Orchard," a play in four acts by Anton Chekhov. Producer and director Victor Stanitsyn, designer L.N. Silich.
New York City Center, February 1965.
Title devised by Library staff.
"Playbill, Volume 2, February 1965, Number 2"--p. [3].
Cast: Alla Tarassova, Larissa Kachanova, Tatiana Lennikova, Pavel Massalzky, Mikhail Zimin, Leonid Guvanov, Mikhail Yanshin, Angelina Stepanova, Alexander Komissarov, Klementia Rostovtseva, Alexei Gribov or Vladimir Popov, Yuri Leonidov, Gregory Konsky, Yuri Nedzvetsky, Alexei Pokrovsky.
LC copy has notations by Coe. Accompanied by torn advertisement flyer for the Friends of the City Center.
In: Richard L. Coe Theater Programs Collection (Library of Congress).
Keywords: Theater programs -- New York (State) -- New York; Theater programs -- 1965.